2009
DOI: 10.1002/ange.200901648
|View full text |Cite
|
Sign up to set email alerts
|

1,n‐Glycols as Dialdehyde Equivalents in Iridium‐Catalyzed Enantioselective Carbonyl Allylation and Iterative Two‐Directional Assembly of 1,3‐Polyols

Abstract: Natures vast collection of polyketide natural products comprises thousands of compounds incorporating polyacetate-derived 1,3-diol or higher 1,3-polyol substructures. Although numerous procedures for the synthesis of these ubiquitous structural motifs have been advanced, [1] the iterative allylmetallation of aldehydes has found exceptionally broad use. [1][2][3][4][5][6] For example, asymmetric iterative allylchromation (Nozaki-Hiyama coupling), [2] allyltitanation, [3] allylstannation, [4] allylsilation, [5] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 101 publications
1
26
0
3
Order By: Relevance
“…Dehydrogenation of the secondary alcohol products is prevented by internal chelation of the homoallylic olefin. Mechanistic studies 8b corroborate the indicated catalytic mechanism wherein carbonyl addition represents the turnover limiting event. These processes embody an inversion of polarity (umpolung) with respect to π-allyl species evident in related allylic substitutions catalyzed by iridium 23 and represent a departure from the longstanding (1978) 24 use of chiral allylmetal reagents in carbonyl addition.…”
Section: Catalytic Enantioselective Alcohol C-h Functionalizationsupporting
confidence: 55%
See 2 more Smart Citations
“…Dehydrogenation of the secondary alcohol products is prevented by internal chelation of the homoallylic olefin. Mechanistic studies 8b corroborate the indicated catalytic mechanism wherein carbonyl addition represents the turnover limiting event. These processes embody an inversion of polarity (umpolung) with respect to π-allyl species evident in related allylic substitutions catalyzed by iridium 23 and represent a departure from the longstanding (1978) 24 use of chiral allylmetal reagents in carbonyl addition.…”
Section: Catalytic Enantioselective Alcohol C-h Functionalizationsupporting
confidence: 55%
“…822 As illustrated in the catalytic mechanism (Scheme 3-A), the internal carboxylate of the ortho - C,O -benzoate moiety maintains neutrality of the π-allyliridium intermediate and, hence, nucleophilic character. Dehydrogenation of the secondary alcohol products is prevented by internal chelation of the homoallylic olefin.…”
Section: Catalytic Enantioselective Alcohol C-h Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The short de novo synthesis of polysubstituted cyclohexenes 23, which are highly functionalized building blocks for novel carbasugar and inositol analogues containing a quaternary center, is an illustration of the synthetic usefulness of the method. While the aforementioned enantioselective bidirectional process developed by Krishe and co-workers [4] is a superior way to obtain pseudo-C 2 -symmetric allylation products, our current [f] Precise diastereomeric ratio could not be determined. The thermal ellipsoids of the X-ray crystal are shown at 35 % probability.…”
Section: Methodsmentioning
confidence: 95%
“…[30] Their synthesis commenced with an efficient iridium-catalyzed double asymmetric carbonyl allylation developed by the Krische group to convert 1,3-propanediol 136 to the C 2 -symmetric diol 138 in 72% yield. [31] The latter was then subjected to the Semmelhack’s palladium-catalyzed alkoxycarbonylation reaction[32] to provide tetrahydropyran 139 in excellent yield and stereoselectivity (d.r. > 20:1).…”
Section: Synthesismentioning
confidence: 99%